Kontektualisasi Pemikiran Machiavelli tentang Kekuasaan-Tujuan Negara - Sri Hastuti Puspitasari (Jurnal Hukum IUS QUIA IUSTUM, 2001)
As thinker who lived in renaissance atmosphere Machiavelly had put his empirical perspective into the end ofstate concept. In his book Prince he tended to focus on how to perpetuate power for the substance ofa state ofa kingdom wasthrone ofa king. Today, even though military power has been used to strengthen a state, the idea of dictatorship would have been going to fade up. At this point, theend ofstate should be based upon political ethicsand moral from this day forward.